Students’ Misconceptions and Mental Models about Floating, Suspension, and Sinking: A Systematic Literature Review - Sarintan Nurcahyati Kaharu; Citra Dewi; Ni Putu Murniasih; Nunuk Haryanti; Supriyatman; Afadil (Jurnal Penelitian Pendidikan IPA, 2026)
This systematic literature review examined research on students’ misconceptions and mental models related to floating, suspending, and sinking (FSS) concepts published between 1990 and 2026. The review aims to map research themes, major forms of misconceptions, classifications of mental models, and instructional interventions used to support scientific understanding. The review implemented the PRISMA framework to identify, screen, and ensure the eligibility of the articles. A total of 215 articles met the inclusion criteria. Findings show that misconceptions remain the most investigated aspect, particularly those involving confusion among density, mass, volume, and buoyant force. Research on mental models is still limited, revealing that many learners rely on initial or synthetic, context-dependent representations rather than scientific models. Instructional interventions are the most extensively and widely investigated, including hands-on activities, conceptual change strategies, simulations, and structured learning models, each contributing differently to addressing misconceptions and promoting scientific mental models about FSS phenomena. Overall, the review highlights persistent conceptual difficulties, insufficient assessment tools, and a need for more integrative research that connects misconceptions, mental models, reasoning, and diagnostic measurement. Strengthening appropriate interventions will support deeper insights into learners’ scientific understanding and mental models of FSS concepts.